TAX SANCTIONS AS A MODERATION OF THE EFFECT OF TAX KNOWLEDGE AND ACCOUNTING INFORMATION ON COMPLIANCE MSME TAXPAYERS IN JAMBI CITY - Anjelika Denya Putri; Ratih Kusumastuti; Imam Ripa’i (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
In pursuit of enhancing tax revenues, particularly from micro, small, and medium enterprises (MSMEs) in Jambi City, fostering honesty, transparency, efficiency, effectiveness, and accountability in tax payment necessitates an analysis of factors influencing voluntary tax compliance among MSME owners. This study aims to investigate the impact of tax knowledge, accounting information, and tax sanctions on taxpayer compliance within the MSME sector in Jambi City. Employing a quantitative approach, this research encompasses a purposive sampling method, with a sample size of 40 respondents selected based on the population of MSMEs in Jambi City. Multiple regression analysis serves as the inferential statistical method for data analysis. Findings indicate that while tax knowledge exhibits no significant influence on taxpayer compliance, accounting information significantly affects compliance. Furthermore, the joint effect of tax knowledge and accounting information significantly influences taxpayer compliance. However, tax sanctions do not moderate the relationship between tax knowledge and taxpayer compliance, whereas they do moderate the impact of accounting information on compliance